(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
The effect of electron and X-ray irradiation on the optical characteristics of CdZnTe/ZnTe quantum-size structures has been investigated. A comparison between the results of both irradiations has shown an essential role of electron excitation in radiation enhancement of Cd diffusion that is one of the reasons for degradation of the II−VI-based quantum-size structures.